Village Funds, Capital Expenditures, and Tax Sharing in Infrastructure Development: Dana Desa, Belanja Modal, dan Pembagian Pajak dalam Pembangunan Infrastruktur - Timbul Sujatmoko; Riyanto Setiawan Suharsono; Abadi Sanosra (Academia Open, 2025)
General Background: Village infrastructure development is pivotal in enhancing community welfare and accelerating regional growth. Specific Background: In Indonesia, funding from Village Funds, Capital Expenditures, and Tax Revenue Sharing serves as a primary driver for such development. Knowledge Gap: However, limited empirical evidence exists on how these funding sources collectively influence infrastructure outcomes, particularly when mediated by retribution mechanisms. Aims: This study investigates the direct and indirect effects of Village Funds, Capital Expenditures, and Tax Revenue Sharing on infrastructure development in Gading District, with retribution as an intervening variable. Results: Using a quantitative approach through surveys and questionnaires in selected villages, the findings reveal that all three funding sources have a positive and significant impact on infrastructure development, while retribution strengthens these relationships. Novelty: This research integrates retribution as a mediating factor, providing a nuanced understanding of financial flows in village-level development. Implications: The study underscores the need for transparent, accountable fund management and enhanced community participation in tax and retribution payments, offering actionable recommendations for strengthening village financial capacity to achieve sustainable infrastructure and welfare improvements. Highlights: Funding sources significantly boost infrastructure growth. Retribution strengthens funding–development links. Transparent management enhances community welfare. Keywords: Village Funds, Capital Expenditures, Tax Revenue Sharing, Infrastructure Development, Retribution Mechanism